Endothelin-1 Levels in Scleroderma Patients: A Pilot Study. (30th July 2013) - Cozzani, Emanuele; Javor, Sanja; Laborai, Erika; Drosera, Massimo; Parodi, Aurora
Abstract : Endothelin-1 (ET-1) is a potent endogenous vasoconstrictor, which mediates vascular wall cells proliferation, fibrosis, and inflammation through two types of ET-1 receptors (ET-A and ET-B). In our retrospective study the serum levels of ET-1 in 18 systemic sclerosis (SSc) patients with and without digital ulcers (DUs) were assessed to observe possible correlation between the levels of ET-1, the evolution of SSc, and the therapy with an ET-1 antagonist (bosentan). In all our patients, the levels of ET-1 were found higher than normal range and correlate with the severity of the disease. Furthermore we also observed that in patients without DUs the levels of ET-1 were higher and did not correlate with new DUs development. In conclusion, the levels of ET-1 in our studied patients do not correlate with the possible development of DUs. The reduction of ET-1 levels in DUs patients in therapy with bosentan confirms the efficacy of this molecule both for treatment and prevention of digital ulcers. The inhibition of ET-A receptor by its antagonist may activate the opposite ET-B receptors, with well-known function ET-1 degradation and reducing of ET-1 serum level as confirmed in our pilot study.